MANAGEMENT OF ATYPICAL MANDIBULAR CORONOID PROCESS ELONGATION WITH BILATERAL INTRAORAL CORONOIDOTOMY - Sıdıka Soydan; Sina Uçkan; Tuba Develi (Cumhuriyet University, 2014)
Bilateral coronoid hyperplasia is characterized by a progressive limitation in mandibular movement secondary to mechanical impingement of the elongated coronoid processes on the posterior surface of the zygomatic bones. The etiology of coronoid hyperplasia remains uncertain, with various proposed theories. As it is an unusual and infrequent clinical entity, hyperplasia of the coronoid process is often overlooked or diagnosed too late. A 27-year old, ASA I, male patient referred to our clinic because of his restricted mouth opening. Bilateral coronoid hyperplasia was detected after detailed temporomandibular joint examination. Restricted mouth opening was successfully treated by bilateral intraoral coronoidotomy with additional physiotherapy. The aim of this case report were emphasizing the mandibular coronoid process elongations as an unignorable differential diagnosis of the asymtomatic mandibular hypomobility cases additionally to the temporomandibular joint and masticator muscles dysfunctions and were describing its successful treatment by intraoral surgery and physiotherapy.